Cytokine Gene Associations With Self-Report Ratings of Morning and Evening Fatigue in Oncology Patients and Their Family Caregivers. (March 2015) - Dhruva, Anand; Aouizerat, Bradley E.; Cooper, Bruce; Paul, Steven M.; Dodd, Marylin; West, Claudia; Wara, William; Lee, Kathryn; Dunn, Laura B.; Langford, Dale J.; Merriman, John D.; Baggott, Christina; et al.
The purpose of this study was to evaluate for differences in variations in pro- and anti-inflammatory cytokine genes between participants who were classified as having low and high levels of morning and evening fatigue and to evaluate for differences in phenotypic characteristics between these two groups. In a sample of 167 oncology outpatients with breast, prostate, lung, or brain cancer and 85 of their family caregivers, growth mixture modeling was used to identify latent classes of individuals based on ratings of morning and evening fatigue obtained prior to, during, and for 4 months following completion of radiation therapy. Differences in single nucleotide polymorphisms and haplotypes in 15 cytokine genes were evaluated between the latent classes. Multiple logistic regression was used to assess the effect of phenotypic and genotypic characteristics on morning and evening fatigue class membership. Associations were found between morning fatigue and number of comorbidities as well as variations in tumor necrosis factor alpha ( TNFA ) rs1800629 and rs3093662. Evening fatigue was associated with caring for children at home and variations in interleukin 4 ( IL4 ) rs2243248 and TNFA rs2229094. Younger age and lower performance status were associated with both morning and evening fatigue. These findings suggest that inflammatory mediators are associated with the development of morning and evening fatigue. However, because different phenotypic characteristics and genomic markers are associated with diurnal variations in fatigue, morning and evening fatigue may be distinct but related symptoms.